Human regulatory T cells lack the cyclophosphamide‐extruding transporter ABCB1 and are more susceptible to cyclophosphamide‐induced apoptosis. Issue 12 (27th October 2014) - Dimeloe, Sarah; Frick, Corina; Fischer, Marco; Gubser, Patrick M.; Razik, Leyla; Bantug, Glenn R.; Ravon, Morgane; Langenkamp, Anja; Hess, Christoph
Abstract : ATP‐binding cassette (ABC) transporters, including ABC‐transporter B1 (ABCB1), extrude drugs, metabolites, and other compounds (such as mitotracker green (MTG)) from cells. Susceptibility of CD4 + regulatory T (Treg) cells to the ABCB1‐substrate cyclophosphamide (CPA) has been reported. Here, we characterized ABCB1 expression and function in human CD4 + T‐cell subsets. Naïve, central memory, and effector‐memory CD4 + T cells, but not Treg cells, effluxed MTG in an ABCB1‐dependent manner. In line with this, ABCB1 mRNA and protein was expressed by nonregulatory CD4 + T‐cell subsets, but not Treg cells. In vitro, the ABCB1‐substrate CPA was cytotoxic for Treg cells at a 100‐fold lower dose than for nonregulatory counterparts, and, inversely, verapamil, an inhibitor of ABC transporters, increased CPA‐toxicity in nonregulatory CD4 + T cells but not Treg cells. Thus, Treg cells lack expression of ABCB1, rendering them selectively susceptible to CPA. Our findings provide mechanistic support for therapeutic strategies using CPA to boost anti‐tumor immunity by selectively depleting Treg cells.